2013
DOI: 10.2169/internalmedicine.52.0220
|View full text |Cite
|
Sign up to set email alerts
|

Antithyroid Drug-induced Agranulocytosis Complicated by Pneumococcal Sepsis and Upper Airway Obstruction

Abstract: Streptococcus pneumoniae is a rare pathogen of sepsis in patients with antithyroid drug-induced agranulocytosis. We herein describe a case of antithyroid drug-induced agranulocytosis complicated by pneumococcal sepsis and upper airway obstruction. A 27-year-old woman who was previously prescribed methimazole for nine months presented with a four-day history of a sore throat. She nearly choked and was diagnosed with febrile agranulocytosis. She was successfully treated with intubation, intravenous antibiotics a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Sepsis is a systemic inflammatory response syndrome (SIRS), which is the number one cause of intensive care unit deaths and a serious problem in adult and pediatric critical care medicine (Ishimaru et al, 2013). In recent years, morbidity associated with sepsis has been rising annually.…”
Section: Introductionmentioning
confidence: 99%
“…Sepsis is a systemic inflammatory response syndrome (SIRS), which is the number one cause of intensive care unit deaths and a serious problem in adult and pediatric critical care medicine (Ishimaru et al, 2013). In recent years, morbidity associated with sepsis has been rising annually.…”
Section: Introductionmentioning
confidence: 99%
“…Review of the literature of reported cases of agranulocytosis between 1999 and 2013 identified 80 cases where the presenting symptoms were described [13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37]. Fever (93.8%), sore throat (68.7%) and chills (21.2%) were the commonest presenting symptoms.…”
Section: Resultsmentioning
confidence: 99%
“…Plantinga et al investigated genetic variants associated with susceptibility to agranulocytosis [1056]. Agranulocytosis is defined as a reduced concentration of granulocytes in peripheral blood (<500 granulocytes/mL blood) [1057,1058]. Agranulocytosis can be induced by various factors, such as anti-psychotic drugs [1059] or antibiotics [1060,1061], but is also observed in rare events (0.1-0.35%) in patients during treatment with thionamides to medicate hyperthyroidism [1062][1063][1064].…”
Section: Role Of Nox3 In Other Diseasesmentioning
confidence: 99%
“…Agranulocytosis can be induced by various factors, such as anti-psychotic drugs [1059] or antibiotics [1060,1061], but is also observed in rare events (0.1-0.35%) in patients during treatment with thionamides to medicate hyperthyroidism [1062][1063][1064]. This anti-thyroid drug-induced agranulocytosis (ATDAC) can be a life-threatening condition [1058,1065], especially after the usage of higher doses of anti-thyroid drugs [1066]. During the conducted GWAS of Plantinga et al, two independent families and six patients with Graves' disease (GD) that developed ATDAC during treatment were analyzed.…”
Section: Role Of Nox3 In Other Diseasesmentioning
confidence: 99%